Analysis of Antimicrobial Drugs Usage Pattern and it’s Cost Analysis in the Pediatric Department of a Tertiary Care Hospital - Shrestha, R.; Koju, P.; Silwal, S.; Karmacharya, B. M.; Shakya Shrestha, S. (Kathmandu University Medical Journal, 2020)
Background Antimicrobials agents are the most widely and often imprudently used therapeutic drugs globally. The pediatric population comprises 20-25% of the total world population, and various acute and chronic diseases are prone to this group. It is also estimated that 50% to 85% of children are prescribed with antimicrobials in developed and developing countries. The misuse of antimicrobials not only contributes not only to the development of antimicrobial resistance but also results in economic burden on the health care system. Objective To analyze the antimicrobial usage and its cost analysis in the Pediatric department of a tertiary care hospital at sub-urban area. Method A hospital based retrospective study was conducted among patient (aged 1 to 18 years) admitted in pediatric ward and intensive care unit for at least 24 hours and dispensed at least one antimicrobial drug from January 2018 to December 2019. Data were collected from electronic medical record using a structured data collection form. The data was entered and analyzed using Microsoft Excel. A descriptive analysis was presented as mean ± (standard deviation) for the continuous variables and frequencies and proportions for categorical variables. Result Among the 1,281 patients, the antimicrobials were prescribed mostly in the respiratory tract infection (39.6%), followed by sepsis (19.75%), enteric fever (11.94%), seizure (10.07%), urinary tract infection (4.29%). Penicillins (1238 times) were highly prescribed followed by Cephalosporin (733 times), Nitro-imidazole (292 times), Aminoglycosides (180 times) and Fluoroquinolones (144 times). During study period in the Pediatric Department, approximately NRs. 1,619,121.11 was spent in the antimicrobial drugs and the highest expenditure was found to be in the Cephalosporin group of antimicrobials (NRs. 530,988.6), followed by Penicillin group of drug (NRs. 3,81,842.2). Conclusion The study concludes that the Penicillin groups of drugs were the most commonly prescribed drug and the highest cost was found to be in Cephalosporin group drugs followed by Penicillin group of drugs.